2013
DOI: 10.1007/s10903-013-9809-5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Migration on the Mental Health of Children Left Behind

Abstract: This study aims to examine the impact of parental international migration on the mental health of children left behind. Data for this paper were taken from the "Child Health and Migrant Parents in South-East Asia, Thailand, 2008" project. A total of 1,030 children (519 from emigrant parents and 511 from non-migrant parents) were covered. Data were collected from the caregivers of children using the Strength and Difficulties Questionnaire. Multivariate analyses were performed to determine the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 22 publications
2
59
1
1
Order By: Relevance
“…According to the urban–rural segregated household registration system, migrant rural workers may live in a city for years without an ‘urban HUKOU’, which is accompanied by barriers to education, housing and health care . The workers had to leave their children in the countryside and entrust them to the care of others, which eventually led to the separation of migrant workers from their children . A new vulnerable group, left‐behind children (LBC), was born.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the urban–rural segregated household registration system, migrant rural workers may live in a city for years without an ‘urban HUKOU’, which is accompanied by barriers to education, housing and health care . The workers had to leave their children in the countryside and entrust them to the care of others, which eventually led to the separation of migrant workers from their children . A new vulnerable group, left‐behind children (LBC), was born.…”
mentioning
confidence: 99%
“…Over the past few decades, many studies have investigated the incidence of mental health problems in LBC, as well as the primary mental health issues that they faced . LBC are in a critical period of mental development, and researchers have found that their mental health is damaged even more than their physical health . Living in unstable family environments, having inadequate parental care and receiving less mental health education from their schools contribute to their poor mental health status .…”
mentioning
confidence: 99%
“…Negative effects were found in different indicators of mental health in children (5,53,54), adolescents (4,6,55), caregivers (26,23), older adults (45,56), wives of the migrants (15,16,25,57), spouses (23) and members of the household in general (58).…”
Section: Effect Of Emigraton or Return Of A Family Member On Health Cmentioning
confidence: 99%
“…For left‐behind children, parental migration may on the one hand improve their well‐being through remittances sent home or on the other, have adverse effects on their lives because of the absence of primary carers (Battistella & Conaco, ; Jia & Tian, ; Lam, Ee, Hoang, & Yeoh, ; Nguyen, Yeoh, & Toyota, ). While a significant share of the scholarship has centred on the impact of parental migration on the children (see, e.g., Adhikari et al, ; Sarma & Parinduri, ; Sun et al, ; C. C. Zhou et al, ), an emerging theme is beginning to focus on exploring children's experiences and perspectives of being left behind (Lam et al, ). This literature has given attention to children's voices and revealed the role—however limited—children play in their family's migration projects (Graham et al, ; Hoang et al, ; Hoang & Yeoh, ; Parreñas, ).…”
Section: Children Migration and Agency: A Brief Review Of The Existmentioning
confidence: 99%